Analisis Faktor Risiko Kematian Bayi di Kecamatan Kupang Barat, Kabupaten Kupang - Imelda F. E. Manurung; Marianus Mau Kuru; Indriati A. Tedju Hinga; Simplexius Asa; Amelya B. Sir (Universitas Nusa Cendana, 2022)
Kupang District is ranked 5 with the highest number of infant mortality in East Nusa Tenggara Province. The total infant mortality 86 and 96 cases in 2018 and 2019, respectively. The purpose of this study was to analyze the risk factors influencing infant mortality in West Kupang Subdistrict. This study used a case-control study design and the respondents were mothers who had babies aged one year old in 2020 with a sample size of 42 people. Data collection used a questionnaire from each variable under the study. The data were analyzed using the chi-square test to see the OR value in order to determine the risk of exposure. The results showed that there was a significant relationship between maternal age during pregnancy (OR= 351; p= 0.000), socioeconomic status (OR= 10.8; p= 0.006) birth weight (OR= 8.2; p= 0.005), premature abnormalities (OR=36; p= 0.000), parity (OR= 5.4; p=0.033), congenital diseases or disorders (OR= 6.6; p=0.000), birth spacing (OR= 8.3; p=0.008), participants in the family planning program (OR= 7.5; p=0.01), antenatal check-up (OR= 8.3; p=0.008), delivery complications (OR= 15; p= 0.000 ), husband's support (OR= 3.8; p= 0.01) with infant mortality. Education and information communication strategies should be improved to create behavior supporting the health of pregnant women and to prevent infant mortality.